A reusable high shear strength electrical adhesive tape and preparation method thereof

By adding specific monomers and functional monomers to the energized mucus-reducing fluid to form chemical bonded electrolytes, the problem of precipitation after energization is solved, and a high shear strength and reusable energized adhesive tape is achieved.

CN118389082BActive Publication Date: 2025-02-11KUNSHAN BYE MACROMOLECULE MATERIAL CO LTD

Patent Information

Application Number
CN202410582477.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-11
Publication Date
2025-02-11
Estimated Expiration
2044-05-11

AI Technical Summary

Technical Problem

The existing power-on and adhesive tape is severely precipitated after power-on, contaminating the patch, making it difficult to reuse, and the colloid shear strength is low.

Method used

By adding acrylate or olefin monomers, methoxy polyethylene glycol-containing esters, functional monomers, organic solvents, salts and initiators to the energized mucus reduction liquid, chemical bonded electrolytes are formed to avoid physical mixing and causing electrolyte precipitates.

Benefits of technology

The high shear strength and reusability of the power-on-adhesive tape are achieved. The peeling force recovery ratio after power-on is greater than 95%, avoiding the large amount of precipitation of electrolytes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118389082B_ABST
    Figure CN118389082B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of adhesive materials, and in particular to a reusable and high shear strength electrical adhesive tape and a preparation method thereof, which is prepared by using acrylic acid esters or olefin monomers, esters containing methoxy polyethylene glycol, acrylic acid, salts, functional monomers, organic solvents, tackifying resins, etc. In the electrical adhesive tape of the present invention, most of the electrolyte is chemically bonded to the main adhesive molecular chain, and part of the electrolyte is dissociated and complexed by the ether oxygen bond strength in the methoxy polyethylene glycol, rather than the simple physical mixing in the prior art, so that a large amount of electrolyte precipitation is effectively avoided when the electrolyte is energized, and the tape can be reused.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adhesive materials, and in particular to a reusable high-shear-strength electrically-induced adhesive tape and a preparation method thereof. Background Art

[0002] The prior art electrically conductive adhesives are mainly prepared by physically mixing adhesive resin, inert organic solvent, and salt (or ionic liquid). For example, the electrolytic adhesive and double-sided tape disclosed in patent CN115895519A are prepared by physically mixing the adhesive body, solid conductive salt, and polar aprotic solvent. They have the problems of severe precipitation after power-on, contaminating the adhered object, being difficult to reuse, and having a large amount of inert solvent and salt (or ionic liquid) added, resulting in low colloid shear strength. Summary of the invention

[0003] In view of the above-mentioned shortcomings of the prior art, the present invention provides a reusable and high shear strength electrically conductive de-viscosity tape and a preparation method thereof, which can effectively solve the above-mentioned problems of the prior art.

[0004] Technical Solution

[0005] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0006] The invention provides an electrified viscosity reducing liquid, which comprises acrylic acid ester or olefin monomers, esters containing methoxy polyethylene glycol and functional monomers.

[0007] Furthermore, it also includes an organic solvent, a tackifying resin, acrylic acid, an initiator, and an aqueous solution containing Li or Na ions; preferably, the aqueous solution containing Li or Na ions is an aqueous solution of lithium hydroxide or sodium hydroxide.

[0008] Further, the acrylic acid ester or olefin monomer includes one or more of methyl acrylate, methyl methacrylate, ethyl acrylate, butyl acrylate, isooctyl acrylate, decyl acrylate, cyclohexyl acrylate, isobornyl acrylate, acrylonitrile, styrene, vinyl acetate, polyurethane acrylate oligomer, polyester acrylate oligomer, epoxy polyacrylate oligomer, ethoxylated phenoxy acrylate, o-phenylphenoxyethyl acrylate, 2-(p-isopropylphenyl-phenoxy)-ethyl acrylate, nonylphenol polyoxyethylene ether acrylate, and ethoxylated ethylhexyl acrylate;

[0009] The ester containing methoxy polyethylene glycol is methoxy polyethylene glycol monoacrylate; the molecular weight of polyethylene glycol in the methoxy polyethylene glycol monoacrylate is 100-2000;

[0010] The acrylic acid includes at least one or both of methacrylic acid and acrylic acid.

[0011] Furthermore, the functional monomer is acrylic acid and esters containing carboxyl, hydroxyl, epoxy or amine groups;

[0012] Preferably, the functional monomer includes one or more of acrylic acid, hydroxypropyl acrylate, hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, glycidyl methacrylate, and acrylamide.

[0013] Furthermore, the organic solvent includes one or both of a high boiling point organic solvent and a low boiling point organic solvent;

[0014] The high boiling point organic solvent includes one or more of propylene carbonate, vinyl carbonate, ethyl methyl carbonate, propylene carbonate, dimethyl carbonate, γ-butyrolactone, vinylene carbonate, and diethyl carbonate;

[0015] The low boiling point organic solvent includes one or more of toluene, benzene, xylene, pentane, hexane, octane, heptane, cyclohexane, cyclohexanone, toluene-cyclohexanone, acetone, methyl butyl ketone, methyl isobutyl ketone, methanol, ethanol, isopropanol, ether, propylene oxide, methyl acetate, ethyl acetate, propyl acetate, and butyl acetate.

[0016] Further, it also includes a salt, and the salt includes one or more of lithium tetrafluoroborate (LiBF4), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium hexafluorophosphate (LiPF6), lithium trifluoromethylsulfonate (LiCF3SO3), lithium bis(trifluoromethylsulfonyl)imide (LiN(CF3SO2)2), lithium bis(oxalatoborate) (LiBOB), sodium perchlorate, sodium tetrafluoroborate, and sodium thiocyanate;

[0017] The tackifying resin includes one or more of maleic rosin, terpene resin, terpene phenol resin, hydrogenated rosin, rosin glycerol ester, C5 petroleum resin, and C7 petroleum resin;

[0018] The initiator includes one or more of lauroyl peroxide, dibenzoyl peroxide, tert-butyl peroxyvalerate, cumene hydroperoxide, azobisisobutyronitrile and azobisisoheptylnitrile.

[0019] Furthermore, by weight, it includes 30-75 parts of acrylate or olefin monomers, 10-30 parts of methoxy polyethylene glycol monoacrylate, 2-20 parts of acrylic acid, 2-15 parts of high boiling point organic solvents, 2-15 parts of salts, 2-10 parts of acrylic acid and ester functional monomers, 50-100 parts of low boiling point organic solvents and 0.1-10 parts of tackifying resins, 0.1-1.5 parts of initiators, and 1-5 parts of aqueous solutions containing Li or Na ions.

[0020] Preferably, by weight, it includes 60-70 parts of acrylate or olefin monomers, 12-18 parts of methoxy polyethylene glycol monoacrylate, 2-8 parts of acrylic acid, 2-8 parts of high boiling point organic solvents, 2-8 parts of salt, 2-8 parts of acrylic acid and ester functional monomers, 80-100 parts of low boiling point organic solvents, 0.1-8 parts of tackifying resin, 0.1-0.5 parts of initiator, and 1-5 parts of aqueous solution containing Li or Na ions. The aqueous solution containing Li or Na ions is an aqueous solution of lithium hydroxide or sodium hydroxide with a concentration of 40-60%; preferably, the aqueous solution containing Li or Na ions is an aqueous solution of lithium hydroxide or sodium hydroxide with a concentration of 50%.

[0021] Preferably, by weight, it includes 65 parts of acrylate or olefin monomers, 15 parts of methoxy polyethylene glycol monoacrylate, 5 parts of acrylic acid, 5 parts of high boiling point organic solvents, 5 parts of salt, 5 parts of acrylic acid and ester functional monomers, 100 parts of low boiling point organic solvents and 5 parts of tackifying resins, 0.3 parts of initiators, and 2 parts of aqueous solutions containing Li or Na ions.

[0022] An electrical viscosity-reducing adhesive is prepared by adding a cross-linking agent to the electrical viscosity-reducing liquid.

[0023] Furthermore, it also includes adding a catalyst to the electrified viscosity reducing liquid;

[0024] Wherein, the crosslinking agent includes one or more of diphenylmethane diisocyanate (MDI), hexamethylene diisocyanate (HDI), toluene diisocyanate (TD I), isophorone diisocyanate (IPD I), dicyclohexylmethane diisocyanate (HMDI), lysine diisocyanate (LD I), an adduct of TD I and trimethylolpropane, IPD I trimer, biuret polyisocyanate, HD I trimer, trifunctional aziridine, ethylenediamine, hexamethylenediamine, diethylenetriamine, triethylenetetramine, and trimethylolpropane triglycidyl ether;

[0025] The catalyst includes one or more of stannous octoate, dibutyltin dilaurate, triethylenediamine, triethylamine, N,N-dimethylbenzylamine, N,N-dimethylhexadecylamine, and N,N-dimethylbutylamine.

[0026] Preferably, 0.1-0.5 parts of a cross-linking agent and 0.01-0.05 parts of a catalyst are added to every 100 parts of the synthesized electrical viscosity-reducing liquid;

[0027] Preferably, 0.3 parts of a cross-linking agent and 0.02 parts of a catalyst are added to every 100 parts of the synthesized electrical viscosity-reducing liquid.

[0028] A powered anti-viscosity tape is prepared by applying the powered anti-viscosity adhesive to the above-mentioned tape; preferably, the powered anti-viscosity adhesive is coated on a release film I, and then the release film II is composited after drying, and then rolled up and matured; preferably, the release films I and II are made of polyethylene (PE), polypropylene (PP) or polyethylene terephthalate (PET).

[0029] Preferably, the difference in release force between the release film I and the release film II is ≥5 gf / 25 mm.

[0030] A method for preparing an electrically conductive adhesive tape, the preparation steps comprising:

[0031] S1. Synthesis of electric viscosity reducing liquid: Add acrylate or olefin monomers, esters containing methoxy polyethylene glycol, acrylic acid, salt, functional monomer, organic solvent and tackifying resin to a reactor, stir evenly, introduce nitrogen to discharge oxygen in the reactor and materials, and heat while stirring. When the temperature of the materials in the reactor rises to 50-70°C, add part of the initiator, then heat to 70-80°C to start timing reaction, react for 3-6 hours, then add the remaining initiator and continue the reaction for 1-3 hours, cool to 35°C-45°C, add 50% concentration of Li or Na ion-containing aqueous solution, stir for 10-30 minutes, and discharge for standby use;

[0032] S2. Preparation of the power-on viscosity-reducing adhesive: Add a crosslinking agent and a catalyst to the power-on viscosity-reducing liquid synthesized in step S1, stir evenly, store below 20-30°C, and set aside;

[0033] S3. Preparation of the electrically conductive adhesive tape: The prepared electrically conductive adhesive tape is applied to the release film I, and then baked in an oven at 70-90°C for 1-4 minutes, and then composited with the release film II, and aged at 30-50°C for 24-72 hours to obtain the electrically conductive adhesive tape protected by the double-sided release film.

[0034] Preferably, a method for preparing an electrically conductive adhesive tape comprises the following steps:

[0035] S1: Synthesis of electric viscosity reducing liquid: 30-75 parts of common acrylic acid ester or olefin monomer, 10-30 parts of methoxy polyethylene glycol monoacrylate, 2-20 parts of (meth) acrylic acid, 2-15 parts of high boiling point organic solvent, 2-15 parts of salt, 2-10 parts of acrylic acid and ester functional monomers containing carboxyl, hydroxyl, epoxy or amino groups, 50-100 parts of low boiling point organic solvent and 0.1-10 parts of tackifying resin are added to a reactor, stirred evenly, non-oxygen inert gas is introduced to discharge oxygen in the reactor and materials, and a certain pressure is maintained, and the temperature is raised while stirring. When the temperature of the material in the reactor rises to 60°C, 0.1-1 parts of initiator are added, and then the temperature is raised to 75°C-80°C to start timing reaction, and the reaction is carried out for 4-5 hours, and then 0.05-0.5 parts of initiator are added to continue the reaction for 2 hours. Cool down to 35-45°C, add 1-5 parts of 50% lithium hydroxide or sodium hydroxide aqueous solution, stir for 20 minutes. Discharge and set aside, the material viscosity is 400-20000cps;

[0036] S2: Preparation of the electrical viscosity-reducing adhesive: add 0.2-20 parts of the cross-linking agent and 0.05-0.2 parts of the catalyst to 100 parts of the synthesized electrical viscosity-reducing electrolyte flooding liquid and stir evenly, store below 25°C for 1-6 hours, and set aside;

[0037] S3: Preparation of the energized anti-viscosity tape: The prepared energized anti-viscosity electrolyte is coated on a 5-100 μm thick release film I, and then baked in an oven at 50°C-90°C for 0.5-2 minutes, and then laminated with a 5-100 μm thick release film II, and then rolled up and aged at 30°C-50°C for 24-72 hours to obtain a double-sided release film protected energized anti-viscosity tape. The thickness of the electrolyte film is 10-200 μm, and the structure is as shown in the attached figure. Figure 1 shown.

[0038] Beneficial Effects

[0039] Compared with the known public technology, the technical solution provided by the present invention has the following beneficial effects:

[0040] In the embodiment of the present invention, most of the electrolytes of the energized viscosity-reducing adhesive are chemically bonded to the main adhesive molecular chain, and part of the electrolytes are dissociated and complexed by the ether oxygen bond strength in the methoxy polyethylene glycol, rather than the simple physical mixing in the prior art. Therefore, a large amount of electrolyte precipitation is effectively avoided when the electrolyte is energized, and the adhesive can be reused. In addition, the strength of the adhesive body is also improved, showing a higher shear strength. In addition, the energized viscosity-reducing tape of the present invention has a peel force recovery ratio of more than 95% when it is laminated after energization. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0042] Figure 1 It is a schematic diagram of the structure of the electrically removable adhesive tape of the present invention.

[0043] The numbers in the figure represent: 1-release film I, 2-adhesive layer, 3-release film II. DETAILED DESCRIPTION

[0044] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0045] The present invention will be further described below in conjunction with the embodiments.

[0046] (I) Tape preparation

[0047] Embodiment 1:

[0048] Step A: Synthesis of the electric viscosity-reducing liquid. 30 parts of isooctyl acrylate, 20 parts of butyl acrylate, 15 parts of methyl methacrylate, 15 parts of methoxy polyethylene glycol (600) monoacrylate, 5 parts of acrylic acid, 5 parts of propylene carbonate, 5 parts of lithium hexafluorophosphate, 5 parts of hydroxyethyl acrylate, 5 parts of rosin glycerol ester, and 100 parts of ethyl acetate are added to a reactor, stirred evenly, nitrogen is introduced to discharge oxygen in the reactor and the materials, and a certain pressure is maintained, and the temperature is raised while stirring. When the temperature of the materials in the reactor rises to 60° C., 0.2 parts of dibenzoyl peroxide are added, and then the temperature is raised to 75° C. to start the timing reaction, and the reaction is carried out for 4 hours. After that, 0.1 parts of dibenzoyl peroxide are added to continue the reaction for 2 hours, and the reaction is cooled to 35° C.-45° C., 2 parts of 50% lithium hydroxide aqueous solution are added, stirred for 20 minutes, and the material is discharged for standby use. The viscosity of the material is 4000-10000 cps.

[0049] Step B: Preparation of the electrical viscosity-reducing adhesive. Add 0.3 parts of HD I trimer and 0.02 parts of dibutyltin dilaurate to 100 parts of the synthesized electrical viscosity-reducing liquid and stir evenly, store below 25°C for later use;

[0050] Step C: Preparation of energized anti-viscosity tape. The prepared energized anti-viscosity adhesive was coated on a 50 μm thick release film I, baked in an oven at 80°C for 3 minutes, and then laminated with a 25 μm thick release film II, and aged at 40°C for 48 hours to obtain a double-sided release film protected energized anti-viscosity tape. The thickness of the electrolyte membrane was 50 μm, and the structure was as shown in the attached figure. Figure 1 shown.

[0051] Embodiment 2:

[0052] Step A: Synthesis of the electric viscosity reducing liquid. 20 parts of isooctyl acrylate, 30 parts of butyl acrylate, 10 parts of styrene, 20 parts of methoxy polyethylene glycol (1000) monoacrylate, 5 parts of acrylic acid, 5 parts of propylene carbonate, 5 parts of lithium hexafluorophosphate, 5 parts of hydroxyethyl methacrylate, 5 parts of terpene resin, and 100 parts of ethyl acetate are added to a reactor, stirred evenly, nitrogen is introduced to discharge oxygen in the reactor and the material, and a certain pressure is maintained, and the temperature is raised while stirring. When the temperature of the material in the reactor rises to 60°C, 0.2 parts of dibenzoyl peroxide are added, and then the temperature is raised to 75°C to start the timing reaction, and the reaction is carried out for 4 hours, and then 0.1 parts of dibenzoyl peroxide are added to continue the reaction for 2 hours, and the temperature is cooled to 35°C-45°C, and the material is discharged for standby use. The viscosity of the material is 4000-10000cps.

[0053] Step B: Preparation of the electrical viscosity-reducing adhesive. Add 0.4 parts of trifunctional aziridine to 100 parts of the synthesized electrical viscosity-reducing liquid, store at below 25°C for later use;

[0054] Step C: Same as step C in Example 1.

[0055] Comparative Example 1:

[0056] Take 100 parts of PS-8281E2 solvent-based acrylic pressure-sensitive adhesive (solid content 49%) from Shimei Chemical, add 20 parts of lithium hexafluorophosphate, 20 parts of propylene carbonate, 10 parts of PX2300A curing agent from Shimei Chemical, 10 parts of terpene resin, 50 parts of ethyl acetate and 50 parts of toluene, stir and disperse evenly. Then prepare a 50 μm thick conductive adhesive tape for electrolyte membrane according to step C in Example 1.

[0057] Comparative Example 2:

[0058] Step A: The same as step A of Example 1, but without adding 15 parts of methoxy polyethylene glycol (600) monoacrylate.

[0059] Step B: Same as step B in Example 1.

[0060] Step C: Same as step C in Example 1

[0061] Comparative Example 3:

[0062] Step A: The same as step A of Example 1, but without adding 5 parts of hydroxyethyl acrylate.

[0063] Step B: Same as step B of Example 1, but without adding 0.3 parts of HD I trimer and 0.02 parts of dibutyltin dilaurate

[0064] Step C: Same as step C in Example 1.

[0065] Comparative Example 4:

[0066] Step A: Same as step A of Example 1, but without adding 5 parts of acrylic acid.

[0067] Step B: Same as step B in Example 1.

[0068] Step C: Same as step C in Example 1.

[0069] Comparative Example 5:

[0070] Step A: Same as step A of Example 1, but without adding 5 parts of propylene carbonate.

[0071] Step B: Same as step B in Example 1.

[0072] Step C: Same as step C in Example 1.

[0073] (II) Performance test

[0074] The following performance tests were performed on the electrically removable adhesive tapes obtained in Examples 1 and 2 and Comparative Examples 1, 2, 3, 4, and 5:

[0075] (1) Surface resistance test (GB / T 1410-2006): Remove one side of the release film from the prepared tape and test the surface resistance of the corresponding adhesive surface.

[0076] (2) 180° peel force test (GB / T 2792-2014): ① Test before power on. After tearing off the release film on one side of the prepared tape, stick it on a steel plate and press it back and forth with a 2kg rubber roller for 3 times. After leaving it at 23°C for 24 hours, test it and record it as F1. ② Peel force test after power on. After tearing off the release film on one side of the tape, stick it on an aluminum foil and press it back and forth with a 2kg rubber roller for 3 times. Then tear off the release film on the other side of the tape, stick it on a steel plate and press it back and forth with a 2kg rubber roller for 3 times. After leaving it at 23°C for 24 hours. Then connect the positive pole of the DC power supply to the aluminum foil and the negative pole to the steel plate. The bonded sample is powered on for 30V*30 seconds, and then the 180° peel force is tested and recorded as F2.

[0077] (3) Shear strength test (GB / T 7124-2008): Remove the release film from the electrolytic adhesive tape and attach it to an aluminum plate substrate. Remove the release film on the other side and attach it to another aluminum plate. The bonding area is 12.5*25mm. After leaving it for 20 minutes, test the shear strength.

[0078] (4) Peel force reversibility test: The sample that has been subjected to the 180° peel force test after power-on is reattached to a new steel plate and rolled back and forth three times with a 2 kg rubber roller. The peel force is tested after being placed at 23°C for 24 hours and recorded as the reattachment peel force F3. The recovery ratio W = F3 / F1*100%.

[0079] (5) Test of residual surface of steel plate after power stripping: Observe the surface contamination of the steel plate for the power stripping test after power is applied to check whether there is oil or residual glue.

[0080]

[0081]

[0082] By testing the examples and comparative examples, the comparative data in Table 1 can be obtained. As can be seen from the data in Table 1, the adhesive tape prepared in Example 1 has a higher shear strength and a better peel force recovery ability after power-on. The peel force recovery ability of the adhesive tapes in the comparative examples is relatively poor, especially the adhesive tapes prepared by the reaction raw materials lacking methoxy polyethylene glycol (600) monoacrylate or functional monomers and crosslinking agents, and the peel force recovery ratio is less than 70%.

[0083] In the embodiment of the present invention, most of the electrolytes of the energized viscosity-reducing adhesive are chemically bonded to the main adhesive molecular chain, and part of the electrolytes are dissociated and complexed by the ether oxygen bond strength in the methoxy polyethylene glycol, rather than the simple physical mixing in the prior art. Therefore, a large amount of electrolyte precipitation is effectively avoided when the electrolyte is energized, and the adhesive can be reused. In addition, the strength of the adhesive body is also improved, showing a higher shear strength. In addition, the energized viscosity-reducing tape of the present invention has a peel force recovery ratio of more than 95% when it is laminated after energization.

[0084] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the protection scope of the technical solutions of the embodiments of the present invention.

Claims

1. An electrified viscosity reducing liquid, characterized in that: In parts by weight, it comprises 30-75 parts of acrylic acid esters, 10-30 parts of methoxy polyethylene glycol monoacrylate, 2-20 parts of acrylic acid, 2-15 parts of high boiling point organic solvents, 2-15 parts of salts, 2-10 parts of acrylic acid and ester functional monomers, 50-100 parts of low boiling point organic solvents, 0.1-10 parts of tackifying resins, 0.1-1.5 parts of initiators, and 1-5 parts of aqueous solutions containing Li or Na ions; Or, by weight, comprising 30-75 parts of acrylate and olefin monomers, 10-30 parts of methoxy polyethylene glycol monoacrylate, 2-20 parts of acrylic acid, 2-15 parts of high boiling point organic solvent, 2-15 parts of salt, 2-10 parts of acrylic acid and ester functional monomers, 50-100 parts of low boiling point organic solvent, 0.1-10 parts of tackifying resin, 0.1-1.5 parts of initiator, and 1-5 parts of aqueous solution containing Li or Na ions; Wherein, the acrylic acid includes at least one or two of methacrylic acid or acrylic acid; The acrylic acid and ester functional monomers include one or more of hydroxypropyl acrylate, hydroxyethyl acrylate, hydroxyethyl methacrylate, and hydroxypropyl methacrylate; The high boiling point organic solvent includes one or more of propylene carbonate, ethylene carbonate, γ-butyrolactone, and vinylene carbonate; The salt includes one or more of lithium tetrafluoroborate (LiBF4), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium hexafluoroarsenate (LiAsF6), lithium hexafluorophosphate (LiPF6), lithium trifluoromethylsulfonate (LiCF3SO3), lithium bis(trifluoromethylsulfonyl)imide (LiN(CF3SO2)2), and lithium bis(oxalatoborate) (LiBOB); The aqueous solution containing Li or Na ions is an aqueous solution of lithium hydroxide or sodium hydroxide.

2. The electric viscosity reducing liquid according to claim 1, characterized in that: The acrylic acid ester or olefin monomers include one or more of methyl acrylate, methyl methacrylate, ethyl acrylate, butyl acrylate, isooctyl acrylate, decyl acrylate, cyclohexyl acrylate, isobornyl acrylate, acrylonitrile, styrene, vinyl acetate, polyurethane acrylate oligomer, polyester acrylate oligomer, epoxy polyacrylate oligomer, ethoxylated phenoxy acrylate, o-phenylphenoxyethyl acrylate, 2-(p-isopropylphenyl-phenoxy)-ethyl acrylate, nonylphenol polyoxyethylene ether acrylate, and ethoxylated ethylhexyl acrylate; The molecular weight of the polyethylene glycol in the methoxy polyethylene glycol monoacrylate is 100-2000.

3. The electric viscosity reducing liquid according to claim 1, characterized in that: The low boiling point organic solvent includes one or more of toluene, benzene, xylene, pentane, hexane, octane, heptane, cyclohexane, cyclohexanone, toluene-cyclohexanone, acetone, methyl butyl ketone, methyl isobutyl ketone, methanol, ethanol, isopropanol, ether, propylene oxide, methyl acetate, ethyl acetate, propyl acetate, and butyl acetate.

4. The energized viscosity reducing liquid according to claim 3, characterized in that: The tackifying resin includes one or more of maleic rosin, terpene resin, terpene phenol resin, hydrogenated rosin, rosin glycerol ester, C5 petroleum resin, and C7 petroleum resin; The initiator includes one or more of lauroyl peroxide, dibenzoyl peroxide, tert-butyl peroxyvalerate, cumene hydroperoxide, azobisisobutyronitrile and azobisisoheptylnitrile.

5. An adhesive that reduces viscosity by electricity, characterized in that: The method is prepared by adding a cross-linking agent to the electrified viscosity reducing liquid according to any one of claims 1 to 4.

6. The electrical viscosity-reducing adhesive according to claim 5, characterized in that: Also included is adding a catalyst to the electrified viscosity reducing fluid; Wherein, the crosslinking agent includes one or more of diphenylmethane diisocyanate (MDI), hexamethylene diisocyanate (HDI), toluene diisocyanate (TDI), isophorone diisocyanate (IPDI), dicyclohexylmethane diisocyanate (HMDI), lysine diisocyanate (LDI), an adduct of TDI and trimethylolpropane, IPDI trimer, biuret polyisocyanate, HDI trimer, trifunctional aziridine, ethylenediamine, hexamethylenediamine, diethylenetriamine, triethylenetetramine, and trimethylolpropane triglycidyl ether; The catalyst includes one or more of stannous octoate, dibutyltin dilaurate, triethylenediamine, triethylamine, N,N-dimethylbenzylamine, N,N-dimethylhexadecylamine, and N,N-dimethylbutylamine.

7. An electrically conductive de-viscosity tape, which is prepared by the electrically conductive de-viscosity adhesive according to claim 6; the electrically conductive de-viscosity adhesive is coated on a release film I, and after drying, a composite release film II is formed, and then rolled up and matured; the release films I and II are made of polyethylene (PE), polypropylene (PP) or polyethylene terephthalate (PET).

8. A method for preparing an electrically conductive adhesive tape according to claim 7, characterized in that: The preparation steps include: S1. Synthesis of electric viscosity reducing liquid: Add acrylates or a mixture of acrylates and olefin monomers, methoxy polyethylene glycol monoacrylate, acrylic acid, salt, acrylic acid and ester functional monomers, high boiling point organic solvents, low boiling point organic solvents and tackifying resins to a reactor, stir evenly, introduce nitrogen to discharge oxygen in the reactor and materials, heat up while stirring, add part of the initiator when the temperature of the materials in the reactor rises to 50-70°C, then heat up to 70-80°C to start timing reaction, react for 3-6 hours, then add the remaining initiator and continue the reaction for 1-3 hours, cool to 35°C-45°C, add a 50% concentration of Li or Na ion-containing aqueous solution, stir for 10-30 minutes, and discharge for standby use; S2. Preparation of the power-on viscosity-reducing adhesive: Add a crosslinking agent and a catalyst to the power-on viscosity-reducing liquid synthesized in step S1, stir evenly, store below 20-30°C, and set aside; S3. Preparation of the energized detackifying tape: The prepared energized detackifying adhesive is coated on the release film I, baked in an oven at 70-90°C for 1-4 minutes, and then composited with the release film II, and aged at 30-50°C for 24-72 hours to obtain a double-sided release film-protected energized detackifying tape.

Citation Information

Patent Citations

  • Electrically peelable pressure-sensitive adhesive composition, electrically peelable pressure-sensitive adhesive product, and method for peeling same

    CN113692434A

Cited By

  • Adhesive device comprising an electro-responsive adhesive able to lower environmental load

    WO2026099159A1